Modeling ways to improve green growth and environmental protection in the context of governance - Pyliavskyi, Iulii; Pushak, Halyna; Molnar, Oleksandr; Dzyana, Halyna; Kushniriuk, Volodymyr (Journal of Environmental Engineering and Landscape Management, 2021)
In recent years, the idea of green growth has been widely discussed not only by experts in environmental economics, but also in various political forums. Many countries use various tools and principles of green growth in their national policies and growth strategies. However, some countries fear that the transition to a green growth model may hamper their development. The article discusses the prerequisites for implementation, the basic principles of green growth into the system of public administration, and also provides a system for modelling ways to implement the principles of green growth using the IDEF0 (functional modeling methodology and a graphical description of the processes) methodology. This methodology allows to clearly see the ways and means of achieving this goal. Considering the importance of the economic component in all processes of monitoring, control and protection of air, water and soil from pollution processes, a system for modeling ways to implement the principles of green growth using the IDEF0 methodology has been formed today is especially relevant.